Tax Reform and U.S. Economic Growth - Jorgenson, Dale W.; Yun, Kun-Young (Journal of Political Economy, 1990)
In this paper we evaluate the impact of the Tax Reform Act of 1986 on U.S. economic growth. We first calculate effective tax rates on income from capital employed in corporate, noncorporate, and household sectors. We then project the future growth of the U.S. economy with and without the 1986 tax reform. We find that much of the potential gain in welfare was dissipated through failure to index the income tax base for inflation. The most promising avenue for future reform is to include income from household assets in the tax base, while reducing tax rates on business income.